Enhancing Vocabulary in 4th Grade Students through Crossword Puzzles: A Quantitative Experimental Study - Dinata, Nur Takdiriyah; Hikmah, Khizanatul (Indonesian Journal of Islamic Studies, 2024)
This study aimed to assess the impact of crossword puzzle media (TTS) on vocabulary enhancement among 4th grade students at SD Muhammadiyah 2 Sidoarjo. Employing a one-group pretest-posttest design, data was collected through observation, test questions, and documentation. The sample consisted of 28 students from class 4 al-farobi. The findings revealed a substantial increase in students' vocabulary, with pre-test and post-test averages of 60.71 and 82.50, respectively. The paired sample t-test confirmed a significant effect (p < 0.05) of crossword puzzles (TTS) on vocabulary enhancement. This study underscores the efficacy of utilizing crossword puzzles as an effective pedagogical tool for augmenting student vocabulary. Highlight: The study demonstrates the positive impact of crossword puzzle media (TTS) on enhancing vocabulary in 4th grade students. Employing a one-group pretest-posttest design, data was collected through varied methods including observation, test questions, and documentation. Significant improvement in students' vocabulary scores, supported by the paired sample t-test (p < 0.05), emphasizes the effectiveness of crossword puzzles (TTS) as a valuable pedagogical tool. Keyword: Crossword Puzzles, Vocabulary Enhancement, 4th Grade Students, Educational Media, Pedagogical Tool